Perception of the population of Santa Maria de Itabira (MG) concerning the implantation of an iron ore mine in the region of Morro Escuro (Research, Society and Development, 2018)
Mining activity represents one of the fundamental sectors for the world economy, acting in the supply of raw materials for the most varied segments and in maintaining the population quality of life. However, mining triggers social, economic and environmental impacts, which require the establishment of policies that allow the development of this activity in a more efficient way. In this context, this research aimed to analyze the perception of Santa Maria de Itabira (MG) population about the implantation of an iron ore mine along the Serra de Morro Escuro and the socioeconomic and environmental impacts resulting from this activity. For that, questionnaires were applied to 371 residents of this municipality. Thus, it was possible to evaluate that despite the population identifies the negative socio-environmental impacts triggered by the mining activity, such as degradation, pollution, deforestation, contamination, accident risk and health problems, a significant portion considers it important to install such activity in the city, given the possibility of job creation and economic growth of the municipality. It is important to carry out new research aimed at understanding the aspirations and perceptions of the different social actors involved in mineral extraction, so that this activity can promote sustainable practices that allow citizens the right to meet their needs without compromising those related to the future generation.